2017
DOI: 10.1121/1.4973313
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of leaky modes in the modal analysis of unbounded problems with perfectly matched layers

Abstract: The modal analysis of wave problems of unbounded type involves a continuous sum of radiation modes. This continuum is difficult to handle mathematically and physically. It can be approximated by a discrete set of leaky modes, corresponding to improper modes growing to infinity. Perfectly matched layers (PMLs) have been widely applied in numerical methods to efficiently simulate infinite media, most often without considering a modal approach. This letter aims to bring insight into the modal basis computed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…2.1, these branch cuts are rotated by an angle equal to −arg(γ) in the case of an infinite PML (for further details, see Ref. [45]). For a PML of finite thickness, this angle becomes equal to −arg(d + hγ) as shown in Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1, these branch cuts are rotated by an angle equal to −arg(γ) in the case of an infinite PML (for further details, see Ref. [45]). For a PML of finite thickness, this angle becomes equal to −arg(d + hγ) as shown in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work [45], the authors have shown that when the surrounding medium is modified by an infinite PML, the forced response can theoretically be obtained with a modal expansion on trapped modes, revealed leaky modes and two continua of radiation modes related to the PML branch cuts. With numerical methods, the PML must yet be truncated to a finite thickness.…”
Section: Context and State-of-the-artmentioning
confidence: 99%
“…More details about the spectrum of open systems using perfectly matched layers can be found in Refs. [33,42,43].…”
Section: Open Waveguide Test Case: Bar Buried Into a Solid Matrixmentioning
confidence: 99%
“…Let us first briefly recall some theoretical results by considering the unbounded problem without introducing any PML. Theoretically, the spectrum of an unbounded problem is constituted by a continuum of radiation modes and proper discrete poles [15,[35][36][37].…”
Section: Spectrum Characteristicsmentioning
confidence: 99%